Borges and I [videorecording] - Wheatley, David (Profile of a writer, 1983)
This presentation weaves together dramatized sequences from Borges stories with a rare interview of the author at his home in Buenos Aires. His writing reveals a trend which has an extra measure of clarity and understanding. The program relates Borges original stories to his personal experience.